FORMATION AND EARLY EVOLUTION OF THE ATMOSPHERE - Marty B.; Dauphas N. (My University, 2002)
The tectonic activity of the Earth allowed exchange of volatile elements (H, C, N, rare gases) between the surface of the Earth (atmosphere, crust, sediments, oceans) and the mantle. However, some of these elements still present elemental and isotopic heterogeneities that allow us to reconstruct the volatile composition of the terrestrial mantle. The protosolar nebula supplied a significant fraction of helium and neon, which were presumably trapped during the major phase of the Earth's accretion and were possibly hosted by accreting dust and/or small porous planetesimals. Surprisingly, volatile elements are in chondritic proportion despite their drastic (10 -3) depletion in the mantle relative to chondrites, in a way that recalls the case of highly siderophile elements. From stable isotope systematics, we find that the contribution of comets to the volatile inventory of the Earth was very limited. The integrated flux of chondritic-like material necessary to provide water, carbon and nitrogen is consistent with that required for the formation of the lunar craters as well as that necessary to account for the inventory of siderophile elements in the mantle. A consequence of this scenario is that the Earth's surface was oxidized very early. Alternatively, volatile and siderophile elements of the mantle could be the remnant of small patches of chondritic material that did not equilibrate with the core nor drastically degas.